(13b-9)-6(2b+1)=-6

Simple and best practice solution for (13b-9)-6(2b+1)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (13b-9)-6(2b+1)=-6 equation:



(13b-9)-6(2b+1)=-6
We move all terms to the left:
(13b-9)-6(2b+1)-(-6)=0
We add all the numbers together, and all the variables
(13b-9)-6(2b+1)+6=0
We multiply parentheses
(13b-9)-12b-6+6=0
We get rid of parentheses
13b-12b-9-6+6=0
We add all the numbers together, and all the variables
b-9=0
We move all terms containing b to the left, all other terms to the right
b=9

See similar equations:

| 1−∑3k=1(9k)29 | | 12(x+13)=12x+156 | | 4(-3n+2)=-4n-8 | | -2x+4=2(4x-)-3(18+4x) | | ∑9k=4(9k)29 | | 15^(-x+7)=16^6x | | 12d3=96 | | 17=5x=+2 | | -3(2x-4)=42 | | 3(x-7)x=2x-21 | | 4n^2+13n+10=0 | | 5y+7=3y+6 | | 32=3v-10 | | 2(5-x)=40 | | (15x+12)=(19x-24) | | 3(1/2x-4/6)=5/2x+5 | | -(7y+1)-(6y-4)=-4 | | 8k+3=11 | | -(4x)=3/4(x-6) | | 0.5X^2+12x-120=0 | | t+13.1=-7.7 | | -7/20f+2/5=1/4f | | -2=3x+11/2 | | 12+7x-21=-8(3-x+4x | | 64=2x-12 | | 6y+24=24 | | |x-8|-3=10 | | -2.8(x4.9)=18.2 | | −2(9x−2)−5(2x−1)=−103 | | -15a+5=-89 | | X^2+14-9x=0 | | 3x-1=-3+2x |

Equations solver categories